The Calculation of Structural Budget Balance : Case of Morocco - Tlidi, Abdelmonaim (International Journal of Economics and Financial Issues, 2013)
In this paper, we present the concept of the structural budget balance and its empirical application on the Moroccan data. For this, we choose the two-step method. In the first step, we estimate the potential production according to Hodrick-Prescott’s method, obtaining the output gap value. This allows us to identify the business cycles of the Moroccan economy during the period 1980-2011. In the second step, we evaluate the sensitivity of the fiscal revenue and the public expenditure to economic activity. The obtained results show that the sensitivity of the fiscal revenue and the public expenditure are very low. We deduce that the budget balance in Moroccan economy is mainly structural and less sensitive to the business cycle. Keywords: Budget balance; Structural budget balance; Hodrick-Prescott method; Potential production JEL Classifications: E62; H62